Bingkai Hukum Negara Indonesia Dalam Perlindungan Hak Ulayat Dan Kesejahteraan Masyarakat Adat Di Daerah Perbatasan - Azis, Yuldiana Zesa; Alputila, Marlyn Jane; Rahail, Emiliana B. (Universitas Musamus, 2024)
This article explores the significance of safeguarding customary rights of indigenous peoples in Indonesia, especially in border regions, with a specific focus on Sota District, Merauke Regency, South Papua. Customary rights, representing the supreme right to land inherited intergenerationally, hold profound social, cultural, and economic value for indigenous communities. Nevertheless, their protection is frequently impeded by agrarian conflicts, deficiencies in the legal system, and the repercussions of climate change. In border areas, customary rights become even more susceptible due to economic interests and the incongruence between government policies and local wisdom. This research employs a qualitative approach, utilizing literature reviews, interviews, field observations, and document analysis, to assess the effectiveness of the legal framework in safeguarding customary rights. Findings indicate that despite a solid legal foundation, the implementation of customary rights protection encounters numerous challenges, necessitating collaborative endeavors from various stakeholders to bolster protection and the well-being of indigenous peoples in border regions.